Plan estratégico para el desarrollo turístico en el Puerto Bajaña del cantón Buena Fe año 2020 - Piedrahita Anchundia, Katherine Michelle (2021)
In good faith we have the tourist center "Puerto Bajaña" that over the years has managed to position itself as one of the best attractions that our canton has, where visitors can enjoy its scenic beauty and its The Bajaña river is the largest tributary, but nevertheless it has not managed to develop touristically as would have been expected, however its development needs a focus to achieve potential in the province. Therefore, the present research aims to determine a strategic plan for tourism development in the "Puerto Bajaña" of the Buena Fe canton of the Los Ríos province, where its main objective will be to achieve tourism progress by enhancing its natural resources. This research implements a series of strategy that allows the development of the tourist center, which will contribute to the local economy of the inhabitants who are indirectly involved in tourist activity, however it will be able to enhance its resources by improving its tourism development.